Elevated exercise blood pressure in middle-aged women is associated with altered left ventricular and vascular stiffness - Sarma, Satyam; Howden, Erin; Carrick-Ranson, Graeme; Lawley, Justin; Hearon, Christopher; Samels, Mitchel; Everding, Braden; Livingston, Sheryl; Adams-Huet, Beverley; Palmer, M. Dean; Levine, Benjamin D. (Journal of applied physiology (1985), 2020)
Women are at increased risk for heart failure with preserved ejection fraction (HFpEF) largely due to higher prevalence of arterial and cardiac stiffening. We were able to identify several subclinical markers of early (stages A and B) HFpEF pathophysiology largely on the basis of exercise blood pressure (BP) response in otherwise healthy middle-aged women. Exercise BP response may be an inexpensive screening tool to identify women at highest risk for developing future HFpEF. Women are at higher risk for developing heart failure with preserved ejection fraction (HFpEF). We examined the utility of peak exercise blood pressure (BP) in identifying preclinical features of HFpEF, namely vascular and cardiac stiffness in middle-aged women. We studied 47 healthy, nonobese middle-aged women (53 ± 5 yr). Oxygen uptake (V̇o 2 ) and BP were assessed at rest and maximal treadmill exercise. Resting cardiac function and stiffness were assessed by echocardiography and invasive measurement (right heart catheterization) of left ventricular (LV) filling pressure under varying preloads. LV stiffness was calculated by curve fit of the diastolic portion of the pressure-volume curve. Aortic pulse-wave velocity was measured by arterial tonometry. Body fat was measured using dual-energy X-ray absorptiometry. Subjects in the highest exercise BP tertile had peak systolic BP of 201 ± 11 compared with 142 ± 19 mmHg in the lowest tertile ( P < 0.001). Higher exercise BP was associated with increased age, percentage body fat, smaller LV size, slower LV relaxation, and increased LV and vascular stiffness. After adjustment, LV and arterial stiffness remained significantly associated with peak exercise BP. There was a trend toward increased body fat and slowed LV relaxation (both P < 0.07). In otherwise healthy middle-aged women, elevated exercise BP was independently associated with increased vascular stiffness and a smaller, stiffer LV, functional and structural risk factors characteristic for stages A and B HFpEF. NEW & NOTEWORTHY Women are at increased risk for heart failure with preserved ejection fraction (HFpEF) largely due to higher prevalence of arterial and cardiac stiffening. We were able to identify several subclinical markers of early (stages A and B) HFpEF pathophysiology largely on the basis of exercise blood pressure (BP) response in otherwise healthy middle-aged women. Exercise BP response may be an inexpensive screening tool to identify women at highest risk for developing future HFpEF.